Performance analysis of dual stator six‐phase embedded‐pole permanent magnet synchronous motor for electric vehicle application. Issue 1 (1st December 2022) - Kumar, Raja Ram; Devi, Priyanka; Chetri, Chandan; Kumari, Ankita; Saikia, Papu Moni; Saket, Ram Khelawan; Kumar, Kundan; Khan, Baseem
Abstract: The motive of this study is to analyse the characteristics of a novel dual‐stator embedded‐pole six‐phase permanent magnet synchronous motor for the application of electric vehicles. A comparative analysis of two separate motor topologies, namely, dual stator embedded‐pole six‐phase permanent magnet synchronous motor and single stator single rotor surface‐mounted permanent magnet synchronous motor, is accomplished to illustrate the performance superiority of the proposed motor. Furthermore, for optimal designing of the proposed motor, a design methodology has also been presented. For the above application, the motor should retain high torque density (HTD) and high reliability. In this regard, a novel H‐Shaped flux barrier is introduced in the rotor portion, which fulfils the requirement of HTD. Moreover, the availability of two sets of the stator winding enhances the performance efficiency and ensures the proposed motor's more significant fault‐tolerating ability of the motor. For performance evaluation, the Finite Element Method analysis is chosen, as it gives appropriate and precise results. From the above analysis, it is concluded that the HTD and the proposed motor's dynamic performance are better than the above‐mentioned conventional motor. Abstract : The motive of this study is to analyse the characteristics of a novel dual‐stator embedded‐pole six‐phase permanent magnet synchronous motor (NDSEPSP‐PMSM) for the application of electric vehicles. A comparative analysis of two separate motor topologies, namely, dual stator embedded‐pole six‐phase permanent magnet synchronous motor (DSEPSP‐PMSM) and single stator single rotor surface‐mounted permanent magnet synchronous motor (SSSRSM‐PMSM), is done to illustrate the performance superiority of the proposed motor.